Skills gap analysis of farmer-owned cooperative directors and its connection to the agricultural landscape - Herchenbach, Jody S. (Kansas State University, 2022)
Agricultural cooperatives are larger and more complex than ever before. Due to this growth, farmer directors need to up-skill to maximize farmer member benefits. Director education is generally considered a successful strategy for improving financial and strategic performance, yet little research has examined the skills farmer cooperative directors need. This research identified skills necessary for farmer cooperative directors to ensure financial and operational success. A two-part approach is taken to address the research objective. The first step follows a qualitative data collection approach using personal interviews and focus groups. Results were consistent across farmer directors and cooperative general managers in Kansas and suggest that successful directors must possess the following skills and behaviors: financial/business, governance, board leadership, industry knowledge and strategic planning. The second step follows a quantitative data collection approach. A survey was designed to identify the farmer cooperative director skill gap, using a Likert scale design, and what skills are most important, using best/worst scaling. We found that directors seem to evaluate themselves at a higher skill level than CEOs/GMs evaluate directors. Most of the skill gaps suggest training opportunities for new directors. The largest skill gaps were found in Cooperative Governance and Policy and Cooperative Finance. Time Management was found as being the least important skill for directors to possess. Asking Critical Questions, Strategic Planning, and Understanding Current Economic and Industry Conditions were consistently in the top three skills with Cooperative Finance and Communication occasionally entering into the top three. Using a Skills Priority Matrix, we found that the same top skills are of highest priority and should, therefore, be the foremost skills training programs are designed to improve moving forward.
Keywords: Farmer cooperatives; Director skills